Analysis Employee Expenditure, Goods and Services Expenditure, Capital Expenditure on the Financial Performance of Regional Apparatus Organisations in Supporting Sustainable Development of the Bangkalan Regency Government - Cakraningrat, Dimas; Sukoco, Agus (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study was conducted to test and analyse the effect of Personnel Expenditure, Goods and Services Expenditure, Capital Expenditure on the Financial Performance of Regional Apparatus Organisations in Supporting Sustainable Development of the Bangkalan Regency Government. Methodolgy: This research uses quantitative methods using 52 populations in 2021-2023 with a total of 156 samples. Findings: The results of testing and analysis carried out, significant and positive results were obtained on the Employee Expenditure, Goods and Services Expenditure variables, while the Capital Expenditure variable obtained significant results with a negative value, which means that the higher the realisation of Capital, the lower the Financial Performance at 52 OPDs in the Bangkalan Regency Government in 2021 - 2023. Paper Type: Research paper